Anti-Shia mass mobilization in Indonesia’s democracy: godly alliance, militant groups and the politics of exclusion - M Khusna Amal (Indonesian Journal of Islam and Muslim Societies, 2020)
This article examines violence against religious minorities, especially Shia groups in the democracy of Indonesia, focusing particularly on the case of the 2016 anti-Milad Fatimah (Fatimah Birth Commemoration) mass mobilization performed by IJABI (The all-Indonesia Assembly of Ahlul Bait Associations) in Bondowoso, East Java, Indonesia. This article finds that the anti-Milad Fatimah mass mobilization involved alliances and conspiracy between Godly Muslim groups with a varied agenda. Sunni militant groups from the Nahdlatul Ulama (NU), FPI (Islamic Defenders Front), Wahabi/Salafi, and Hizbut Tahrir Indonesia (HTI) groups, which merged into FOKUS (Ahlus Sunnah Wal Jama'ah Communication Forum), were the main protagonists who played a key role in driving mass mobilization. Unlike previous studies that understood the anti-Shia movement merely as a form of affirming Islamic orthodoxy, this study finds evidence that there were wider agendas than the theological ones. Excluding the Shia from capturing Islamic public space, and challenging religious authority and local power which was dominated by moderate Muslim groups, were the socio-political agendas which contributed to the anti-Milad Fatimah mass mobilization. The involvement of radical Islamist groups such as the activists of the Tarbiyah and HTI is a sign that there is a strong political agenda behind mass mobilization. However, the ultimate goal of applying Islamic Sharia will never fade from the religious movements of Islamist groups.Studi ini mengkaji kekerasan terhadap minoritas agama khususnya kelompok Shia di Indonesia era demokrasi. Tulisan memilih kasus aksi mobilisasi massa anti-Milad Fatimah yang dilaksanakan oleh IJABI (Ikatan Jama’ah Ahlul Bait Indonesia), Bondowoso, Jawa Timur pada 2016. Tulisan ini memeroleh temuan yang menarik bahwa aksi mobilisasi massa anti-Milad Fatimah, melibatkan aliansi longgar di antara kelompok-kelompok Godly Muslim dengan agendanya yang tidak tunggal. Kelompok-kelompok militant Sunni dari kalangan NU, FPI, Wahabi/Salafi dan HTI, yang menggabungkan diri ke dalam FOKUS (Forum Komunikasi Ahlus Sunnah wal Jama’ah), merupakan aktor-aktor utama yang berperan penting dalam memobilisir aksi massa tersebut. Berbeda dari kajiankajian yang umumnya memahami gerakan anti-Shi’ah sebagai bentuk peneguhan ortodoksi Islam atupun homogenisasi Islam Indonesia, studi ini mendapati temuan yang jauh lebih besar dan kompleks dari sekedar agenda teologis itu. Mengekslusi Shi’ah dari ruang public Islam dan menantang otoritas keagamaan dan kekuasaan local yang didominasi oleh kelompok-kelompok Muslim moderat merupakan sejumlah agenda sosio-politik yang turut mewarnai aksi massa itu. Keterlibatan kelompok-kelompok Islamisme radikal seperti aktivis Gerakan Tarbiyah dan Hizbut Tahrir Indonesia (HTI), menjadi sinyalemen cukup kuat adanya agenda politis di balik aksi massa. Bagaimanapun, imaginasi dan citacita penerapan syari’at Islam tidak akan pernah pudar dari gerakan keagamaan kelompok-kelompok Islamis.